The Principal’s Strategy in Improving Teacher Performance Through Strengthening Educational Human Resource Management - Triantoro, Rilo Pambudi; Mawardi, Muhammad Febri; Arnafama, Putri Medina; Safitri, Aulia; Aslamiah, Aslamiah; Suriansyah, Ahmad (FKIP - Universitas Riau, 2026)
This study aims to analyze and formulate an effective Principal’s strategic model for improving teacher performance through the strengthening of an integrated Educational Human Resource Management (EHRM) cycle. The method employed is a literature study (library research), conducted through thematic synthesis and content analysis of 15 reputable journals published within the period 2015–2025. The synthesis results indicate that optimal improvement in teacher performance is achieved through the implementation of Principal-led strategies driven by Transformational Leadership and focused on three pillars of EHRM: (1) Needs-Based Planning (Needs Assessment); (2) Internal Continuous Professional Development (CPD), such as Lesson Study and Coaching, which function as Intellectual Stimulation; and (3) a Formative Evaluation System supported by Strategic Rewards. These findings successfully formulate a Principal Strategic Model (PSM) in the strengthening of EHRM that is cyclical and integrated. This study concludes that the success of the Principal as a strategic leader lies in the ability to integrate all EHRM functions to create a school culture conducive to continuous professional growth, which ultimately directly enhances teacher performance and commitment.